Integration of Minimum Initial Service Package for Reproductive Health in the Sister Village Program - Hermawan, Dwi Yunanto; Widyaningrum, Heny; Lee, Sook Foong; Indarjo, Sofwan; Nugroho, Efa; Raharjo, Bambang Budi; Nisa, Alfiana Ainun; Ediyarsari, Puput; Wahyono, Bambang; Isniyati, Heni; Wasono, Edi; Prihatno, Bayu Eko; Rozali, Agus (Jurnal Kesehatan Masyarakat, 2023)
Indonesia’s high Disaster Risk Index (DRI) encourages the government to pay extra attention to disaster management efforts. MISP must be available in health crises because the need for reproductive health services remains and increases during the disaster response period because 4% of the affected people are pregnant women, and 75% are women, adolescent girls, and children. Integrating MISP into the Sister Village program is very important as an effort to reduce the impact of disasters on reproductive health due to the disruption of health services. This research was carried out in 2022 to explore opportunities and obstacles to integrating MISP in the sibling village program. The research uses a qualitative design with a phenomenological approach. Data collection used Focus Group Discussion techniques with 10 informants who were stakeholders related to the research topic. The research results show that in the integration of MISP and the Sister Village program, the role of each stakeholder is very important to achieve program objectives. Cooperation and coordination between stakeholders is the key to success. The integration of MISP in the Sister Village program can increase community participation in reproductive health services, strengthen the relationship between the health sector and the development sector, and improve public awareness of the importance of reproductive health. Limited accessibility and infrastructure in remote villages, stigma and cultural problems in village communities, lack of support and attention from the government and related parties, as well as security and conflict problems in several areas are obstacles to the integration of this program. High Disaster Risk Index (DRI) Indonesia encourages the government to pay extra attention to disaster management efforts. MISP must be available in health crises because the need for reproductive health services remains and increases during the disaster response period because 4% of the affected people are pregnant women, and 75% are women, adolescent girls, and children. Integrating MISP into the Sister Village program is very important as an effort to reduce the impact of disasters on reproductive health due to the disruption of health services. This research was carried out in 2022 to explore opportunities and obstacles to integrating MISP in the sibling village program. It uses a qualitative design with a phenomenological approach. Data collection used Focus Group Discussion techniques with 10 informants who were stakeholders related to the research topic. The research results show that in the integration of MISP and the Sister Village program, the role of each stakeholder is very important to achieve program objectives. Cooperation and coordination between stakeholders is the key to the success of the program. The integration of MISP in the Sister Village program can increase community participation in reproductive health services, strengthen the relationship between the health sector and the development sector, and improve public awareness of the importance of reproductive health. Limited accessibility and infrastructure in remote villages, stigma and cultural problems in village communities, lack of support and attention from the government and related parties, as well as security problems and conflicts in several areas, are obstacles to the integration of this program.